In-vitro evaluation of synthetic dye decolourisation by filamentous ascomycetous fungi isolated from freshwater environments in Sri Lanka and development of a prototype for addressing environmental pollution from synthetic dye contamination - Wimalasena, Madhara K.; Wijayawardene, Nalin N.; Dharmarathne, Susan B.; Gunasekara, Nimesha M.; Ekanayake, Manavi S.; Jayalal, R. G. Udeni; Bhat, Jayarama D.; Dawoud, Turki M.; Zhang, Gui-Qing; Weerasinghe, Damith C.; de Zoysa, Heethaka K. S.; Dai, Dong-Qin; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Mycoremediation emerges as an alternative strategy for decolourisation of synthetic dyes and is valued for its cost-effectiveness and environmentally friendly attributes. Five fungal strains, Aspergillus sp.1, Lasiodiplodia crassispora, L. pseudotheobromae, Neopestalotiopsis saprophytica, and Trichoderma sp.1, isolated from freshwater environments in Sri Lanka, were subjected to decolourisation of 100 mg L-1 of Congo Red (CR), Crystal Violet (CV), Malachite Green (MG), and Safranin dyes, frequently discharged into the environment from laboratories and industries. Screening of the decolourisation ability of isolated fungal strains was conducted in both solid and liquid media containing Potato Dextrose Agar (PDA) and Potato Dextrose Broth (PDB) for ten days incubation period and 14–28 days, respectively, at 30 °C. The liquid media screening processes showed that L. pseudotheobromae exhibited the highest decolourisation percentage for CV (95.23% ± 0.82) and MG (93.12% ± 0.36). L. crassispora demonstrated the highest decolourisation abilities for CR (91.45% ± 0.20) and Safranin. All fungal strains successfully achieved over 60% decolourisation of CV, CR, and MG. However, Safranin showed the lowest decolourisation by all isolated strains, except for L. crassispora (70.46% ± 1.18). Considering the overall results in both solid and liquid media (exceeding 70%), L. crassispora exhibited the highest decolourisation ability among all selected dyes. Besides, the results in liquid media were reconfirmed by the screening process on solid media. The results of the present study showed that mycoremediation for synthetic dye decolourisation should be expanded to outdoor settings. Leveraging this insight, a prototype was developed for real-world application, creating a microencapsulation system for mycoremediation. This innovative system offers a sustainable alternative to traditional physicochemical treatments for wastewater management, specifically on laboratory discharges.